Optimisasi Carbopol Sebagai Basis Gel pada Gel Antiseptik Berbasis Alkohol: Optimization of Carbopol as a Gel Base in Antiseptic Gel Alcohol Based - Noor Linda Febrianie (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Alcohol-based antiseptic gels are considered to be able to replace washing hands with soap and can inhibit the growth of viruses. Alcohol-based gels have the disadvantage of being difficult to mix with gel-based ingredients. Carbopol as an alcohol-soluble gel base was chosen to be the base for this alcohol-based antiseptic gel. The concentrations used were 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, and 2%. The physical test of the gel was carried out to see the optimum carbopol gel base for alcohol-based antiseptic gel. Physical test includes organoleptic observation, pH value, viscosity determination spreadability test and homogeneity test. The results obtained from organoleptic observation showed that the gel was clear, smelled antiseptic, two concentrations had a slightly sticky and sticky consistency. The pH value yields a pH range of 4.65 - 6.06. The viscosity results showed a viscosity range of 10.48725 - 21.18107 Pa.S. The Spreadability test shows the spreadability range of 6.07 - 7.03 cm. The homogeneity test resulted in an alcohol-based antiseptic gel without coarse particles. Hedonic organoleptic test produced the most preferred antiseptic gel was the antiseptic gel with a carbopol concentration of 1.25%. The results showed that the optimal carbopol was used as a gel base in an alcohol-based antiseptic gel 1.25% carbopol.